Basicity as a Thermodynamic Descriptor of Carbanions Reactivity with Carbon Dioxide: Application to the Carboxylation of α,β-Unsaturated Ketones - Franceschi, Pietro; Nicoletti, Catia; Bonetto, Ruggero; Bonchio, Marcella; Natali, Mirco; Dell’Amico, Luca; Sartorel, Andrea (Frontiers in Chemistry, 2021)
The utilization of carbon dioxide as a raw material represents nowadays an appealing strategy in the renewable energy, organic synthesis and green chemistry fields. Besides reduction strategies, carbon dioxide can be exploited as a single carbon atom building block, through its fixation into organic scaffolds with the formation of new C-C bonds (carboxylation processes). In this case, activation of the organic substrate is commonly required, upon formation of a carbanion C-, being sufficiently reactive towards the addition of CO2. However, the prediction of the reactivity of C- with CO2 is often problematic, with the process being possibly associated to unfavourable thermodynamics of the reaction. In this contribution, we present a thermodynamic analysis combined with density functional theory calculations on 50 organic molecules that enable to achieve a linear correlation of the standard free energy (DG0) of the carboxylation reaction with the basicity of the carbanion C-, expressed as the pKa of the CH/C- couple. The analysis identifies a threshold pKa of ca 36 (in CH3CN) for the CH/C- couple, above which the DG0 of the carboxylation reaction is negative and indicative of a favourable process. We then apply the model to a real case involving electrochemical carboxylation of flavone and chalcone, as model compounds of alfa,beta-unsaturated ketones. Carboxylation occurs in beta-position from the doubly reduced dianion intermediates of flavone and chalcone (calculated DG0 of carboxylation in beta = -12.8 and -20.0 Kcalmol-1 for flavone and chalcone, respectively, associated to pKa values for the conjugate acids of 50.6 and 51.8, respectively). Conversely, the one-electron reduced radical anions are not reactive towards carboxylation (DG0 > +20 Kcalmol-1 for both substrates, either in alfa or beta position, consistent with pKa of the conjugate acid < 18.5). For all the possible intermediates, the calculated pKa and DG0 of carboxylation are consistent with the linear correlation model developed. The application of the DG0 vs pKa correlation is also discussed for alternative reaction mechanisms and for carboxylation of other C=C and C=O double bonds. These results offer a new mechanistic tool for the interpretation of the reactivity of CO2 with organic intermediates.